Kajian Estetik Batik Jombangan Motif Jula-Juli sebagai Petuah Kehidupan dalam Bermasyarakat - Kholis, Achmad Nur; Budi, Setyo; Nurcahyanti, Desy (Institut Seni Indoensia Surakarta, 2023)
A Batik is a work of art that has a teaching value in the form of advice. The aim of this study was to determine the aesthetic value of visualizing Jula-Juli batik as a guide in society. The research method used to collect and present the data is descriptively qualitative. The aesthetic value assessment approach uses the elegant design theory of Luca Iandoli and Giuseppe Zello. Data were collected using observation, interviews and documentation of Jula-Juli Batik as a medium for preserving local wisdom in the form of advice with novelty value.Keyword: batik, aesthetic value, Jombang, local wisdom, motifs